In Utero and Lactational Exposure Study in Rats to Identify Replacements for Di(2-ethylhexyl) Phthalate - Thomas C. Nardelli (Nature Portfolio, 2017)
Abstract Di(2-ethylhexyl) phthalate (DEHP) and other phthalates are ubiquitous environmental contaminants with endocrine disrupting properties. Two novel plasticizers, 1,4 butanediol dibenzoate (BDB) and dioctyl succinate (DOS), have been proposed as potential replacements. Both have desirable properties as plasticizers and minimal in vitro biological effects. Herein, we present an in utero and lactational exposure study comparing DEHP with BDB, DOS, and 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH), a commercial alternative. Timed-pregnant Sprague-Dawley rats were gavaged with vehicle or one of these chemicals at 30 or 300 mg/kg/day from gestational day 8 until postnatal day (PND) 21. The offspring were examined for effects on developmental and endocrine markers until PND 46. DEHP treatment (300 mg/kg) decreased heart weights in dams and induced a significant decrease in anogenital index and an increase in hemorrhagic testes and multinucleated gonocytes in PND 3 male pups. An increase in the incidence of hemorrhagic testes was also observed on PND 8 after exposure to DINCH (30 and 300 mg/kg). The only other effects observed were decreases in serum alanine transaminase and magnesium in BDB 30 exposed dams. These data suggest that both BDB and DOS are viable alternative plasticizers.